Birth weight is assessed from mother's weight gain during pregnancy and quality pregnancy examinations in Jombok Village Pule District Trenggalek Regency - Wulandari, Anggrawati; Yukitama, Dian (Journal of Midwifery and Nursing, 2024)
Birth weight is one measure of the success of health programs, related to the risk of disease and child survival. The weight gain of pregnant women will affect the weight gain of the fetus. ANC is very important for detecting infant abnormalities during the neonatal period. The aim of this research was to determine the effect of maternal weight gain during pregnancy and quality pregnancy examinations on birth weight in Jombok Village, Pule District, Trenggalek Regency. This research design uses a survey method with a cross sectional approach, the research sample is 30 respondents, using accidental sampling techniques and measuring instruments in the form of questionnaires. The independent variables are Weight Gain for Pregnant Women, and Quality Pregnancy Examination, the dependent variable is Birth Weight. Data analysis used Multiple Linear Regression Test with a significant value (p ? 0.05). The results of the research show that there is an influence of weight gain in pregnant women and quality pregnancy examinations on birth weight with a significance value (p) of 0.001b (p < 0.05), so it is stated that H1 is accepted. Quality pregnancy checks (at least 6 times) will increase the mother's knowledge about her pregnancy and detect all risks to pregnancy and danger signs. Health workers need an active role in quality pregnancy checks and monitoring pregnant women's weight gain to achieve normal birth weight.